2021
DOI: 10.1021/acs.est.1c03092
|View full text |Cite
|
Sign up to set email alerts
|

Recent Update on UV Disinfection to Fulfill the Disinfection Credit Value for Enteric Viruses in Water

Abstract: Ultraviolet (UV) radiation alone or in combination with other oxidation processes is increasingly being considered for water disinfection because of stringent regulatory requirements for pathogen inactivation. To fulfill this requirement, an appropriate UV dose or fluence (mJ/cm2) is applied to combat enteric viruses in surface or treated water. There is a need for a cumulative review on the effectiveness of current and emerging UV technologies against various types of human enteric viruses. We extracted the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…A volunteer study showed that norovirus remained infectious for at least 61 days in a spiked groundwater at room temperature in the dark (using an original dose of ~ 6.5 × 10 8 genomic equivalent copies) but was limited due to the cohort size (Seitz et al, 2011 ). Surrogate viruses such as murine norovirus, feline calicivirus and Tulane virus exhibit different sensitivities to inactivation, disinfection and/or anti-viral agents (Augsburger et al, 2021 ; Knight et al, 2016 ). Data from only molecular testing methods, including those utilising an intercalating dye such as propidium monoazide may not accurately inform on infectivity, as results depend largely on the mode of inactivation (Leifels et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A volunteer study showed that norovirus remained infectious for at least 61 days in a spiked groundwater at room temperature in the dark (using an original dose of ~ 6.5 × 10 8 genomic equivalent copies) but was limited due to the cohort size (Seitz et al, 2011 ). Surrogate viruses such as murine norovirus, feline calicivirus and Tulane virus exhibit different sensitivities to inactivation, disinfection and/or anti-viral agents (Augsburger et al, 2021 ; Knight et al, 2016 ). Data from only molecular testing methods, including those utilising an intercalating dye such as propidium monoazide may not accurately inform on infectivity, as results depend largely on the mode of inactivation (Leifels et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…When applied to clear, low‐particulate effluents such as RO permeates, UV and UV‐AOP processes can reliably achieve very high pathogen removal based on known relationships between UV dose and pathogen log removal (USEPA, 2006). Consistent with these dose/response relationships, reported log removals of enteric viruses range from 1 to 6 for UV systems in the 10–100 mJ/cm 2 dose range (Hijnen et al, 2006), and >6 for AOP processes at 400 mJ/cm 2 and above (Augsburger et al, 2021). Within the lower range (non‐AOP) dosing range, the variability in observed LRVs is partially attributable to the varying UV sensitivity of different viruses, with adenoviruses showing particular resistance to UV and generally having the lowest inactivation rate constants (Hijnen et al, 2006).…”
Section: Treatment Process Monitoringmentioning
confidence: 66%
“…However, the efficiency of cavitation for the disinfection of SARS-CoV-2 has not been investigated. Adenoviruses which have been reported to be resistant to UV irradiation (Augsburger et al, 2021), and monochloramination (Gall et al, 2016), are inactivated by both ozonation and photocatalysis disinfection (Chen et al, 2021a). Furthermore, Chen et al (2021b) mentioned that inactivation of E. coli, Clostridium perfringens, Vibrio cholerae, and MS2 was faster using chlorine-active substances produced on-site compared to chlorine.…”
Section: Comparison Of Disinfection Methodsmentioning
confidence: 99%